“Imagine, maths is used anywhere, and we don’t get to know this”—upper secondary students and the relevance of advanced mathematics - Vos, Pauline; Wiik, Anders; Hernandez-Martinez, Paul (Frontiers in Education, 2024)
People are more motivated to put effort into learning when they know they will be able to put the learnt content to use. These relevance perceptions play a motivating role in the learning of mathematics, a subject renowned for its abstraction, hard examinations, and usefulness in many fields in society (research, industries, etc.). In this article, we describe a study on upper secondary students in an advanced mathematics course and their perception of the relevance of mathematics in future professions, in particular regarding two concepts in their curriculum (logarithms, trigonometry). We defined relevance as a connection between an object (relevance of what?), a subject (relevant for whom?), an asserter (relevant according to whom?), and a purpose (relevant to what end?). The aim of the study was to know (1) what relevance perceptions students held regarding the advanced abstract mathematical concepts, and (2) how students can develop these considering that students do not yet know exactly what future is ahead of them. We interviewed pairs of students (n=14, 17-19 years old) in two parts. The first part of the interview revealed that students learned mathematics within a traditional school culture that emphasized practice-and-drill of pure mathematics and that did not in any way inform students about the use of mathematics in research and workplaces. After exposing students to authentic applications of logarithms and trigonometry, the second part of the interview showed the power of imagination when it connected students to future professions for which mathematics was relevant. Instrumental in effectively prompting students’ imagination were visualizations showing applications of the mathematical concepts within workplace contexts. Drawing on Leont’ev’s version of Activity Theory, we theorize students’ assertions of the relevance of mathematics through the dialectics of self and collective (relating one’s own goals and more general motives), the dialectics of use-value and exchange-value (needing mathematics for later life or for examinations), and the dialectics of mathematization and de-mathematization (whilst mathematics is used in many workplaces, it is hidden in instruments).